Comparative Study of Port Business Characteristics with Maritime Logistics Approach in Ports: Shanghai, Singapore, Busan, and Rotterdam - Dradjati Dewiatena, Angela; Nur Bahagia, Senator (Pelopor Publikasi Akademika, 2023)
The port is one of the freight transportation activities of business locations through the surrounding water area. The approach to port business characteristics can be approached with maritime logistics. Maritime logistics presents an integrated concept of planning, implementing, and managing the movement of goods and information in sea transportation. The three key players that make up the maritime logistics system at a port are shipping, port/terminal operations, and freight forwarding. This article examines several major ports: Shanghai, Singapore, Busan, and Rotterdam, for comparison based on the characteristics of the port business side. Comparative studies are carried out with a benchmarking process against reference ports.